Gene Polymorphisms Increasing the Risk of Intracranial Aneurysms: Interleukin-6 -174G>C and -572G>C (Part II) - Giotta Lucifero , Alice; Baldoncini, Matias; Brambilla , Ilaria; Rutigliano, Monica; Savioli, Gabriele; Galzio, Renato; Campero, Alvaro; Lawton, Michael T.; Luzzi, Sabino (Acta Biomedica Atenei Parmensis, 2022)
IntroductionThe interleukin-6 (IL-6), a proinflammatory cytokine, supports the adaptive immune response and regulates inflammatory processes. The -174 G>C and -572 G>C promoter polymorphisms of the IL-6 gene take part in the pathogenesis of intracranial aneurysms (IAs) and influence the clinical presentation of subarachnoid hemorrhage.This meta-analysis purposes to evaluate whether and which IL-6 allelic variations are related to a risk of IAs formation.MethodsA PRISMA-based literature search was performed on the PubMed/Medline and Web of Science databases. The keywords used were “interleukin-6,” “IL-6,” “polymorphism,” “interleukin-6 genotype,” combined with “intracranial aneurysms” and “subarachnoid hemorrhage.” Only human case-control studies, with a study (IAs) and a control group, written in English, and published in the last 15 years were selected. A meta-analysis was performed, estimating odds ratios and 95% confidence intervals in fixed- or random-effects models, as applicable. Statistical analysis was conducted with RevMan 5.0 software.Results9 studies were eligible. No associations were found between -174 G>C polymorphisms and IAs susceptibility. Notable results were reported by the analysis of -572G>C polymorphisms. -572GG/GC/CC genotypes were strongly related to IAs occurrence with a statistical significance of p=0.03, p=0.0009, and p=0.00001, respectively.ConclusionA higher incidence of -572G>C promoter polymorphisms were demonstrated in the IAs group, highlighting the pivotal role of inflammatory genes in the natural history of brain aneurysms.Additional studies are required considering the racial heterogenicity and the need to widen the population sample.